2015
DOI: 10.4314/ijbcs.v9i2.13
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable production in Togo and potential impact of pesticide use practices on the environment

Abstract: In West Africa, market gardening is considered one of the sectors in agriculture that consumes lots of pesticides. In order to study (i) the principal protection practices of vegetables and (ii) the inherent environmental risks to pesticide use practices, a survey was carried in Togo from 2010 to 2011. A random selection of 161 farmers were interviewed on their farms, which are distributed over the most important vegetable production sites located in dry Savanna, forests and littoral zones of Togo. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 5 publications
0
21
0
3
Order By: Relevance
“…Finally, efforts should be made at the national, regional and international level to promote the use of biological approaches for the management of invasive pests in African agriculture, which is often dominated by chemical control, including the use of highly restricted pesticides [17,45].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, efforts should be made at the national, regional and international level to promote the use of biological approaches for the management of invasive pests in African agriculture, which is often dominated by chemical control, including the use of highly restricted pesticides [17,45].…”
Section: Discussionmentioning
confidence: 99%
“…Agriculture is the main source of income for most of the population of Togo (70%) [6] and to date agricultural practices are expanding in rural areas and in city outskirts. Indeed, many studies reported that in Togo crop protection practices are primarily based on the excessive use of synthetic pesticides, which in most cases includes pyrethroids and organophosphates [36, 37]. Agboyi et al [37] reported that farmers still use organochlorides, although they are obsolete.…”
Section: Discussionmentioning
confidence: 99%
“…In African countries, the farmers' practices in the use of the pesticides are not predictable due to lack of proper training or knowledge. Consequently, the non-observance of good agricultural practices, especially the abusive use of agricultural inputs such as pesticides are frequently observed on farms (Agboyi et al, 2015). Farmers may use any pesticides even if they are banned or not recommended for particular uses provided they are available for other applications and they function well on the control of pests or if they are cheap.…”
Section: Introductionmentioning
confidence: 99%